ANALISIS POLA PERSEBARAN DAN KETERJANGKAUAN SMA/SMK DI KOTA SALATIGA MENGGUNAKAN ANALISIS BUFFERING & NEAREST NEIGHBOR - Vincent Sapakoly; Frederik Samuel Papilaya (Program Studi Sistem Informasi, Universitas Banten Jaya, 2023)
In Salatiga City, namely at the SMA & SMK levels, this study intends to examine the accessibility, distribution pattern, and affordability of educational facilities. In this study, buffering analysis, nearest neighbor analysis, and quantitative descriptive data analysis were employed as the methodology. The information utilized was collected from INAGeoportal, Indonesia's national geoportal that links numerous Ministries, Institutions, Provinces, and Regions that collaborate with Google Earth to connect the National Geospatial Information Network. The result of this study shows that The distribution of high schools and vocational education institutions in Salatiga City is categorized as a cluster pattern with a nearest neighbor index of 0.52, according to the results of nearest neighbor analysis using average nearest neighbor formula in ArcGIS Pro App and according to buffering analysis, it is recognized that all the school at the highschool levels in Salatiga region are reachable.